Study of the phenology and seed productivity of golden root (Sedum roseum (L.) Scop.) in the Central region of the Non‐chernozem zone of the Russian Federation - О. M. Savchenko; E. Yu. Babaeva (Юг России: экология, развитие)
Aim. The study of the phenology and seed productivity of golden root plants in the 2nd‐4th years of life in the Moscow region under the influence of meteorological conditions. Methods. The objects of research were plants of golden root from the biocollection of VILAR in Moscow. The studies included field and laboratory experiments, which conducted in 2016‐2019 according to methods adopted in medicinal plant production. Weather conditions in the Moscow region during the research period were identified on the Internet. Seed productivity was assessed according to generally accepted methods. Determination of seed sowing qualities was carried outaccording to National Standard 34221‐2017.Results. The influence of weather conditions on the passage of phenological phases of young golden root plants in 2016‐2019 in the Non‐chernozem zone of the Russian Federation under experimental field conditions was studied for the first time. The duration of phenological phases depending on conditions in the year of observation was determined. The composition of the population of young golden root plants for the second, third and fourth years of vegetation wasestablished. Adverse factors which reduce seed productivity and affect the quality of seeds were identified.Conclusion. The favourable meteorological characteristics of the growing season contributed to an increase in the mass of 1000 seeds by an average of 43 mg and increased seed germination to 82%. Differences in seed quality and productivity of seeds depending on the conditions of the year of observation may indicate the necessity for measures for adaptation of the plants to harmful environmental factors.